Ontogeny and nutritional programming of the hepatic growth hormone-insulin-like growth factor-prolactin axis in the sheep - Hyatt, M.A.; Budge, H; Walker, D; Stephenson, T; Symonds, Michael E. (Endocrine Society, 2007)
The liver is an important metabolic and endocrine organ in the fetus but the extent to which its hormone receptor (R) sensitivity is developmentally regulated in early life is not fully established. We, therefore, examined developmental changes in mRNA abundance for the growth hormone (GH) and prolactin (PRL) receptors (R) plus insulin-like growth factor (IGF)-I and –II and their receptors. Fetal and postnatal sheep were sampled at either 80, or 140 days gestation, 1, 30 days or six months of age. The effect of maternal nutrient restriction between early to mid (i.e. 28 to 80 days gestation, the time of early liver growth) gestation on gene expression was also examined in the fetus and juvenile offspring. Gene expression for the GHR, PRLR and IGF-IR increased through gestation peaking at birth, whereas IGF-I was maximal near to term. In contrast, IGF-II mRNA decreased between mid and late gestation to increase after birth whereas IGF-IIR remained unchanged. A substantial decline in mRNA abundance for GHR, PRLR and IGF-IR then occurred up to six months. Maternal nutrient restriction reduced GHR and IGF-IIR mRNA abundance in the fetus, but caused a precocious increase in the PRLR. Gene expression for IGF-I and –II were increased in juvenile offspring born to nutrient restricted mothers. In conclusion, there are marked differences in the developmental ontogeny and nutritional programming of specific hormones and their receptors involved in hepatic growth and development in the fetus. These could contribute to changes in liver function during adult life.